Antagonistic activity of Xylaria sp. and Neopestalotiopsis egyptiaca against three tree pathogens - Boon Sieng, Chan Thip (2018)
Fusarium oxysporum, Ceratocystis fimbriata and Phellinus noxius are pathogenic fungi and causal agent of disease to plantation and forest tree. Chemical fungicides are commonly used to control these pathogen, but they are not environmental friendly. As alternative, biological control agents are being sought to replace chemicals. In this study, the growth performance and morphological characteristics of two endophytic fungal (Xylaria sp. and Neopestalotiopsis egyptiaca) and three fungal pathogens (C. fimbriata, P. noxius and F. oxysporum) were examined. They were inoculated on Potato Dextrose Agar (PDA) : 1) normal PDA (aPDA). and 2) PDA with adjusted pH values between 7.2-7.4 (nPDA).The growth of N. egyptiaca was faster than Xylaria sp. growth, while the growth of F. oxysprorum was three times and two times faster than C. fimbriata and of P. noxius respectively. The antagonistic activity was determined through dual culture assay and non-volatile compound assay. Xylaria sp. was a better pathogen inhibitor compared to N. egyptiaca. Based on percentage inhibition of radial growth (PIRG) value Xylaria sp. could inhibit three tree pathogens while N. egyptiaca only could inhibit P. noxius and less effective to control the growth C. fimbriata and F. oxysporum. This shows that between these two endophytic fungi isolates, Xylaria sp. has potential as biological control agents against tested fungal pathogens.